Violence and Harassment in Politics as a Specific Way of Violencen against Women - Soriano Moreno, Silvia (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2019)
The existing inequality in the access of women and men to political positions, in the institutions and in the political parties, makes necessary to consider the causes of the situation, in order to analyse the possible ways of improvement. Traditionally, the focus has been on policies and measures aimed at parity democracy, improving the conditions of access to institutional politics and establishing gender quotas in institutions. However, even though the situation improves timidly, it is not the only problem that we face to achieve equality in this area. Because the problem is not only that women do not reach the spaces of political power, but when they arrive they don’t remain.One of these possible causes can be because of the resistances that women find when they access, or attempt, to hold political charges and manifests itself through a specific form of violence against women: violence or harassment in politics.To study this, it will be necessary to address the experience that comes to us from Latin America, where this specific form of violence has been worked for several years and can provide us with interesting data and results that we must take into account to address the issue.
Keywords: politics; institutions; violence; harassment; women